Los mercaderes de la muerte en Colombia: multinacionales y derechos humanos (2016)
For over fifteen years, several regions have suffered serious human rights violations and breaches of IHL. Thousands of peasants, union leaders and political leaders have been killed, disappeared, displaced, forced into exile, and so on, but who are the perpetrators of such violations? On today's globalized world the conflict actors remain the same for other times?, Does the crime has evolved and progressed to other areas?, What factors make people who commit such violations are likely to be held responsible?All of the above questions, try to be addressed in this article where it's being from theoretical sources on the principles and functioning of markets be closer to the Colombian reality, especially multinational corporations act Chiquita Brands, Dole, Del Monte and Drummond, from operating in Colombia, more than eighty years, in the case of Chiquita Brands. This is to prove that these companies, as higher denominations of paramilitary leaders in Colombia have had no qualms about paying these illegal armed groups to end just with the participation of workers and communities in decisions their environment.In this regard million Colombians, belonging to the most vulnerable groups of Colombian society, die, disappear, are tortured, displaced, exiled, etc. As a result of the actions of multinationals established in our country that not only leverage our resources and our workforce at a very low price, but that fund illegal groups to commit the most serious human rights violations, in order to expand and increase profits.We try to show the magnitude of the negative consequences caused by the multinationals in our territory and the other possible scenarios to go in search of justice against such violations. Thus, the lack of speed and efficiency of the Colombian justice against the actions of such multinationals in our territory, refers to another mechanism we have had to use the victims of these companies: American podium with basis for the "ALIEN TORT CLAIM ACT CLAUSE - ATCA - foreign torts in violation of the law of nations, statute that prohibits and punishes the serious human rights violations of United States nationals abroad or foreigners in the U.S. territory.This is the only way that specific field of human rights violations victims can make use of events caused by these companies in Colombia, as the United States has been characterized as a country reserved the ratification of various human rights instruments and international humanitarian law, as the Rome Statute.However, lack of internal regulations regarding human rights violations as mentioned above, various court decisions have been based on the Act on Liability for Damage to Aliens (Alien Tort Claims Act or ATCA, Alien Tort Statute)